2018
DOI: 10.1021/acs.jced.8b00549
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Vanadium Phosphorus Oxide into TiO2 Matrix for Selective Adsorption of Methylene Blue from Aqueous Solution

Abstract: Vanadium phosphorus oxide (VPO) has been embedded in a titania matrix. The adsorption capacity of the VPO­(5–30 wt %)@TiO2 composites and VPO alone for the removal of harmful cationic and anionic dyes such as methylene blue (MB), rhodamine B (RhB), and methyl orange (MO) have been extensively investigated. The FT-IR, XRD, TGA, FE-SEM, EDX, and BET techniques were applied for characterization of the adsorbents. Batch-adsorption experiments demonstrated that the VPO­(30 wt %)@TiO2 as the best composite selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…9b). The negative amount of ΔS indicated decreased randomness at the solid/solution interface during the process of sorption [50,51]. The negative values of ΔH and ΔS showed that hydrogen bonds and VDW force were the principal forces governing binding in the MB-CQDs/HMS system [45].…”
Section: Effects Of Temperature and Thermodynamic Studiesmentioning
confidence: 99%
“…9b). The negative amount of ΔS indicated decreased randomness at the solid/solution interface during the process of sorption [50,51]. The negative values of ΔH and ΔS showed that hydrogen bonds and VDW force were the principal forces governing binding in the MB-CQDs/HMS system [45].…”
Section: Effects Of Temperature and Thermodynamic Studiesmentioning
confidence: 99%
“…Dye wastewater from various industries has posed a serious threat to the ecological environment and human health due to its high toxicity and non-biodegradability [ 1 ]. Methylene blue (MB), as an artificial organic cationic dye, is widely used as a colouring agent and redox indicator [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] Some synthetic dyes can cause damages to the ecological environment and human beings. [ 3 ] For example methylene blue (MB) which has negative effect on human health as it can cause eye burning, difficulties in breathing, increase heart rate, cause nausea, mental confusion, and methemoglobinemia. [ 4 ] Some of applied strategies for remediation of organic pollutants in wastewater are coagulation, reverse osmosis, ion exchange, sedimentation, filtration, adsorption, chemical oxidation, biodegradation, photodegradation, and ozonation methods.…”
Section: Introductionmentioning
confidence: 99%